Pelatihan Pajak Bagi Para Pelaku Usaha Mikro Kecil dan Menengah di Bekasi - Martogi Marojahan Sitinjak; Hubertus Maria Rosariandoko Wijanarko; Asri Zaldin (Universitas Teknologi Yogyakarta, 2025)
Many Micro, Small and Medium Enterprises (MSMEs) in Bekasi, West Java, do not have adequate understanding and skills regarding their tax obligations. This lack of understanding is generally due to the lack of training they have received in relation to taxation facilities for MSMEs. Nationally and regionally, MSMEs play a vital role in the Indonesian economy. In supporting the growth and sustainability of this sector, the central government, through the Directorate General of Taxes (DGT) has implemented a taxation scheme specifically designed for MSME players, namely the MSME Final Income Tax (PPh), which apparently has not been widely understood by MSME entrepreneurs in Bekasi. This Community Service activity aims to socialize and train MSME players in the Bekasi area in understanding the policy background, tax subjects and objects, calculation of Final Income Tax for MSMEs, tax payment and tax reporting for MSME players.